Localized climate change impacts on tourism businesses - Frank W. Milbourn V; Ethan R. Wertlieb; Robert W. Orttung (Annals of Tourism Research Empirical Insights)
Climate change models are becoming increasingly granular, making it possible to predict how specific tourist destinations will be affected according to four different greenhouse gas emission scenarios, ranging from current levels of emissions to enhanced mitigation measures. For a popular destination like France, the changing flows of domestic and international tourists will have a strong impact on local businesses. This research makes a methodological innovation by helping tourism-oriented businesses predict how climate change will affect their specific location in terms of temperature changes and economic impacts. By using European National Meteorological and Hydrological Services data combined with the CMIP6 climate models, we can show with greater granularity than before the different reactions of international and domestic tourists to these new climate trends and the differing impacts on the seasonality of when tourists will visit different destinations across France. The empirical results show that fewer international tourists, who spend more money per capita than domestic tourists, will visit southern France in the summer months, but that their numbers will increase at other times of the year. Changes among domestic tourists are less pronounced. Although overall tourism to France is expected to increase, fewer international visitors will arrive under climate futures defined by fossil-fuel driven scenarios than more sustainable ones. To achieve the best results, businesses in host communities should place climate mitigation measures at the center of practices and policies to navigate the impact of increasing temperatures and tourist reactions.